Phase transitions in the Mitsui model - Dublenych, Yu.I. (Condensed Matter Physics, 2011)
In this paper, phase transitions in the Mitsui model without longitudinal field but with a transverse one are investigated in the mean field approximation. The one-to-one correspondence has been established between this model and the two-sublattice Ising-type model with longitudinal and transverse fields. Phase diagrams and diagrams of existence of the ferroelectric phase are constructed. In the case Ω = 0 (Ω is the transverse field), a simple analytical expression for the tricritical temperature and the condition of existence of the tricritical point are obtained. For Ω ≠ 0, systems of equations for the tricritical point and for the condition of its existence are written. В роботi в наближеннi середнього поля дослiджено фазовi переходи в моделi Мiцуi
без поздовжнього поля, проте з поперечним полем. Встановлено взаємооднозначну залежнiсть мiж такою моделлю та двопiдґратковою моделлю типу Iзiнга з поздовжнiм
i поперечним полями. Побудовано фазовi дiаграми та дiаграми областей iснування сегнетофази. Для випадку Ω = 0 (Ω–поперечне поле) одержано простий аналiтичний вираз для трикритичної температури й умову iснування трикритичної точки. Для Ω 6= 0 записано системи рiвнянь для трикритичної точки й умови її iснування.